Factors That Affect The Quality Of Financial Reports - Muhammad Arif Setyo Nugroho; Muhyarsyah Muhyarsyah; Nurul Hidayah (Syntax Idea)
The research conducted aims to analyze and prove empirically the effect of leverage, profitability, institutional ownership, managerial ownership, independent board of commissioners, and audit committees on the quality of financial reports (study of manufacturing companies listed on the Indonesian stock exchange for the period 2015-2020). This research is based on secondary data obtained from the company's annual and financial reports. There were 60 companies out of a total of 193 companies in this study, which used a purposive sampling technique to determine the sample. As for data processing in this study, using multiple linear regression analysis methods and processed with Microsoft Excel and IBM SPSS Statistics 25.0 software. The research results show that (1) Leverage has a significant positive effect on the quality of financial reports. (2) Profitability has a significant negative effect on the quality of financial reports. (3) Institutional ownership has no significant effect on the quality of financial reports. (4) Managerial ownership has a significant positive effect on the quality of financial reports. (5) The board of independent commissioners has a significant negative effect on the quality of financial reports. (6) the audit committee has a significant negative effect on the quality of financial reports.